Survey-based cross-country comparisons where countries vary in sample design: Issues and solutions - Olena Kaminska; Peter Lynn (University of Essex, Institute for Social and Economic Research (ISER), 2016)
In multi-national surveys different countries usually implement different sample designs. When making estimates of differences between countries, analysts often fail to take sample design appropriately into account. This failure is sometimes because variables indicating stratification, clustering or weighting are unavailable, partially available, or in a form unsuitable for cross-national analysis. We demonstrate how complex sample design should be taken into account when estimating differences between countries and we provide practical guidance to analysts and to data producers. Using EU-SILC data for 19 countries, we evaluate the inverse mis-specification effect (imeff) that results from ignoring aspects of design. Our empirical findings illustrate the importance of incorporating appropriate sample design indicators in variance estimation.
Keywords: C83; D10; Q50; 330; cross-national surveys; design effect; mis-specification effect; multi-stage sampling; standard errors; stratified sampling